Pengelolaan Sampah Organik dan Pemberdayaan Siswa Dengan Teknik Kompos Takakura - Rasyid, Djusmadi; Rante, Anshar; Warda, Warda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Waste management in boarding school environments, such as Pondok Tahfizh Al-Qur’an Daarul Furqon Palopo, faces significant challenges due to the accumulation of organic waste, which can negatively impact health and the environment. Therefore, systematic interventions are necessary to empower students in waste management using efficient and eco-friendly methods, such as Takakura composting. This community service initiative aims to enhance students' knowledge and skills in organic waste management through education, training, and mentoring, supported by pre- and post-tests to evaluate the effectiveness of the intervention. The program involved 41 participants aged 12-19, primarily junior high school students. The results demonstrated a significant increase in knowledge following the intervention, with 85.4% of participants classified as having moderate knowledge before the education, and 100% achieving a good level of knowledge after the training. The Wilcoxon test yielded a p-value of 0.00, indicating a significant impact of the education and training provided. Based on these findings, it can be concluded that Takakura-based composting in boarding schools is crucial for maintaining environmental cleanliness and empowering students to adopt eco-friendly practices. Sustainable waste management in boarding school environments can be achieved through intensive education and training, engaging students as agents of change.